22β-hydroxytingenone induces apoptosis and suppresses invasiveness of melanoma cells by inhibiting MMP-9 activity and MAPK signaling. (1st March 2021) - Aranha, Elenn Suzany Pereira; Portilho, Adrhyann Jullyanne de Sousa; Bentes de Sousa, Leilane; da Silva, Emerson Lucena; Mesquita, Felipe Pantoja; Rocha, Waldireny C.; Araújo da Silva, Felipe Moura; Lima, Emerson Silva; Alves, Ana Paula Negreiros Nunes; Koolen, Hector Henrique Ferreira; Montenegro, Raquel Carvalho; Vasconcellos, Marne Carvalho de
Abstract: Ethnopharmacological relevance: 22 β -hydroxytingenone (22-HTG) is a quinonemethide triterpene isolated from Salacia impressifolia (Miers) A. C. Smith (family Celastraceae), which has been used in traditional medicine to treat a variety of diseases, including dengue, renal infections, rheumatism and cancer. However, the anticancer effects of 22-HTG and the underlying molecular mechanisms in melanoma cells have not yet been elucidated. Aim of the study: The present study investigated apoptosis induction and antimetastatic potencial of 22-HTG in SK-MEL-28 human melanoma cells. Materials and methods: First, the in vitro cytotoxic activity of 22-HTG in cultured cancer cells was evaluated. Then, cell viability was determined using the trypan blue assay in melanoma cells (SK-MEL-28), which was followed by cell cycle, annexin V-FITC/propidium iodide assays (Annexin/PI), as well as assays to evaluate mitochondrial membrane potential, production of reactive oxygen species (ROS) using flow cytometry. Fluorescence microscopy using acridine orange/ethidium bromide (AO/BE) staining was also performed. RT-qPCR was carried out to evaluate the expression of BRAF, NRAS, and KRAS genes. The anti-invasiveness potential of 22-HTG was evaluated in a three-dimensional (3D) model of reconstructed human skin. Results: 22-HTG reduced viability of SK-MEL-28 cells and caused morphological changes, as cell shrinkage, chromatin condensation, and nuclear fragmentation. Furthermore, 22-HTG caused apoptosis, which was demonstrated by increased staining with AO/BE and Annexin/PI. The apoptosis may have been caused by mitochondrial instability without the involvement of ROS production. The expression of BRAF, NRAS, and KRAS, which are important biomarkers in melanoma development, was reduced by the 22-HTG treatment. In the reconstructed skin model, 22-HTG was able to decrease the invasion capacity of melanoma cells in the dermis. Conclusions: Our data indicate that 22-HTG has anti-tumorigenic properties against melanoma cells through the induction of cell cycle arrest, apoptosis and inhibition of invasiveness potential, as observed in the 3D model. As such, the results provide new insights for future work on the utilization of 22-HTG in malignant melanoma treatment. Graphical abstract: Image 1 Highlights: Apoptosis was the death pathway of SK-MEL-28 cells treated with 22 β -hydroxytingenone. 22 β -hydroxytingenone promoted mitochondrial dysfunction without ROS generation. 22 β -hydroxytingenone inhibited expression of BRAF, NRAS, and KRAS genes. 22 β -hydroxytingenone reduced invasion of SK-MEL-28 cells in reconstructed skin model.